2017
DOI: 10.1007/s11136-017-1669-3
|View full text |Cite
|
Sign up to set email alerts
|

A study of dyadic interdependence of control, social participation and occupation of adults who use long-term care services and their carers

Abstract: Purpose Unpaid care is an important source of support of people with long-term conditions. Interdependence of carers’ and care recipients’ quality of life would be expected due to the relational nature of caregiving. This study aims to explore interdependence of quality of life in carer/care-recipient dyads, especially in relation to mutual interdependence due to social feedback in the caregiving relationship and also the partner effects of one partner’s experience of long-term care support on the other’s outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 56 publications
(52 reference statements)
1
22
0
Order By: Relevance
“…Finally, this study did not conduct dyadic interviews with informal caregivers. Studies involving the voices of caregivers’ point towards the existing differences in the various actor's perceptions (Brimblecombe, Pickard, King, & Knapp, ; Turcotte et al, ) and indicate that caregivers’ and care recipients’ rating of control over their daily life are mutually interdependent (Rand, Forder, & Malley, ). Another study explored dyadic associations of mastery beliefs among older partners and suggested that partners’ mastery beliefs matter for the health (behaviours) of older adults (Drewelies, Chopik, Hoppmann, Smith, & Gerstorf, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study did not conduct dyadic interviews with informal caregivers. Studies involving the voices of caregivers’ point towards the existing differences in the various actor's perceptions (Brimblecombe, Pickard, King, & Knapp, ; Turcotte et al, ) and indicate that caregivers’ and care recipients’ rating of control over their daily life are mutually interdependent (Rand, Forder, & Malley, ). Another study explored dyadic associations of mastery beliefs among older partners and suggested that partners’ mastery beliefs matter for the health (behaviours) of older adults (Drewelies, Chopik, Hoppmann, Smith, & Gerstorf, ).…”
Section: Discussionmentioning
confidence: 99%
“…14 The ASCOT-Carer was developed to reflect the social care policy and legislative focus on informal caregivers' wellbeing and QoL, 15 which recognizes that caregivers are co-clients of LTC along with the people they support. [16][17][18][19] The ASCOT-Carer is included in the Adult Social Care Outcomes Toolkit (ASCOT), 3 a suite of instruments designed to measure LTC-related QoL of recipients [20][21][22] and informal caregivers. 14,[16][17][18][19] The ASCOT-Carer and an instrument for LTC recipients incorporate multiple dimensions of QoL that can be improved by LTC, for example, control over daily life, personal safety, and social participation.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] The ASCOT-Carer is included in the Adult Social Care Outcomes Toolkit (ASCOT), 3 a suite of instruments designed to measure LTC-related QoL of recipients [20][21][22] and informal caregivers. 14,[16][17][18][19] The ASCOT-Carer and an instrument for LTC recipients incorporate multiple dimensions of QoL that can be improved by LTC, for example, control over daily life, personal safety, and social participation. 14,[16][17][18][19][20][21][22] The ASCOT-Carer and LTC recipient instruments have 4 overlapping QoL dimensions: control over daily life, social participation, personal safety, and occupation ("doing things I find value in and enjoy").…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the impact of social care services may be through the impact on the care-recipient (e.g. home care may improve the carerecipient's QoL and, thereby, also the carer's QoL) via the mutual dependence in utility between the cared-for person and their carer (Becker, 1981;Van Houtven and Norton, 2004;Rand et al, 2017).…”
Section: Introductionmentioning
confidence: 99%